An Atlas of Mitral Valve Imaging - Desai, Milind; Jellis, Christine; Yingchoncharoen, Teerapat (Springer London : Imprint: Springer, 2015)
This Atlas provides readers with a case-based overview of mitral valve structure and echocardiographic evaluation. The clinical scenarios illustrate how the various echocardiographic parameters provide incremental value in the accurate assessment of mitral valve dysfunction. Detailed, noninvasive assessment of the mitral valve remains integral for planning and performance of mitral valve surgery. Increasingly, echocardiographic assessment and real-time guidance are also required to facilitate percutaneous treatment options. We highlight important imaging aspects of these cases, along with salient teaching points and further recommended reading.   An Atlas of Mitral Valve Imaging will be particularly useful for readers as a contemporary instructional review of the various imaging techniques. The book also provides numerous video files that can be used to test understanding of the real-world imaging appearance of the mitral valve. A wide range of conditions are included to illustrate the breadth of mitral valve pathology and the challenges faced in acquiring optimal images.  .